GAMBARAN KEMAMPUAN INTERPERSONAL PETUGAS ON BOARD PT. TRANSJAKARTA - Laurensia Natalia; Angela Oktavia Suryani; Dhevy Setya Wibawa (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2016)
The mobility of people in Jakarta is increasing every year. Meanwhile, the availability of public transportation has not been able to accommodate the needs of its population. So many people in Jakarta use of private vehicles which create traffic congestion every day. Therefore, since 2014, Jakarta's local government provide a transportation facility, Transjakarta bus. This transport system prioritizes the comfort, security, and safety of service users. To achieve these objectives, at every Transjakarta fleet placed the officers on board who are asked to facilitate and to fulfill the customer demands and needs. Seeing the importance of the role of the officer on board, it is necessary for them to be equipped with interpersonal skills. Therefore, this research aims to describethe levels of interpersonal skills of officers on board of PT. Transjakarta.This research is using quantitative approach with data collection techniques implied is the interpersonal skills measurement tool consists of five domains: the ability to start a relationship, assertive abilities, the ability to give emotional support, the ability to manage and control conflicts, and the ability to open up. The research conducted with 115 participants of officers on board PT. Transjakarta. The data analyses using statistic descriptives. The results indicate that the interpersonal skills of the officers on board PT. Transjakarta both overall and per domain is on the average level. The results show that it is important to take into account the interpersonal skills of the on board officers of PT Transjakarta, either by considering the factors on recruiting the new officers or by developing the skills of existing officers. The limitations of this study are the general criterias of participants and the long work tenure of the participants.